Book review: Higginbotham, P. (2017). Children's Homes: A History of Institutional Care for Britain's Young, Barnsley: Pen & Sword. 256pp. ISBN: 9781526701350 - Ben Quail (Scottish Journal of Residential Child Care)
The history of children in care in the United Kingdom is long and fractured. Peter Higginbotham's work Children's Homes: A History of Institutional Care for Britain's Young is an attempt to look at the history of children's establishments and the providers of children's services in the United Kingdom. He reflects on how these institutions functioned and progressed amidst the changing attitudes of the populace and the considerations put forward over how best to accommodate the wants and needs of children in care over the course of several centuries.